Honor Among Lovers Based on a Story by Austin Parker - Parker, Austin (Universal Pictures, 2017)
Screen legends Claudette Colbert and Fredric March star in "Honor Among Lovers", an intense romantic drama from trailblazing female director Dorothy Arzner. An office flirtation turns deadly when secretary Julia Traynor's (Colbert) jealous husband Philip Craig (Monroe Owsley) questions the nature of her relationship with her former boss Jerry Stafford (March). This Pre-Code Hollywood classic features a star-studded supporting cast including Ginger Rogers, Charles Ruggles and Pat O'Brien. [Cover]
Keywords: DVD-Video